Integrative Perinatal Management Enhanced the Advantage of Prenatal Diagnosis on Critical Pulmonary Valve Stenosis: An Observational Preliminary Study - Li, Jiawen; Li, Gang; Shi, Xiaoqing; Wang, Chuan; Duan, Hongyu; Zhou, Kaiyu; Hua, Yimin; Li, Yifei (Frontiers in Pediatrics, 2020)
Background: Percutaneous balloon valvuloplasty (PBPV) is recommended as a first-choice treatment for critical pulmonary stenosis (CPS). A concept of perinatal integrative management has been developed. Unfortunately, the evidence on the advantage of integrative management for CPS during the perinatal period is absent. Methods: Single-center, observational, preliminary research has been developed, and three groups have been enrolled. There were 42 children with CPS enrolled for this study between January 2014 and December 2017 in our center, and their follow-up duration is at least 1 year. Three groups were set up: the integrative perinatal management group (group I), who received prenatal diagnosis with perinatal management to maintain circulation and an optimized PBPV procedure; the prenatal diagnosis group (group PR), who received a diagnosis of pulmonary stenosis before birth without any monitoring and perinatal management; and the postnatal diagnosis group (group PO), who received the CPS diagnosis after birth. Result: There were 13 patients enrolled in group I, 11 babies enrolled in group PR, and 18 cases included in group PO. Integrative management helped to put the timing of PBPV in advance. The age for PBPV in group I was 9.38 ± 5.58 days, and groups PR and PO were 24.54 ± 4.87 and 49.11 ± 9.50 days, respectively. The average peak transvalvular gradient (PGs) of the perinatal management group (group I) and prenatal diagnosis group (group PR) remained at a stable level. However, the average PGs of group PO were progressively elevated during follow-up. Moreover, the follow-up data from group I revealed an advantage in RV development and functional restoration. There was no difference among the three groups in the ratio of reintervention and postoperative moderate pulmonary regurgitation during 1-year follow-up (p >0.05). Conclusion: Prenatal diagnosis helps to improve the outcomes of PBPV. Moreover, perinatal integrative medical management enhances the advantage of prenatal diagnosis. However, this research is still a small-size cohort study, and the limited population number and follow-up duration were the major limitations to expand the conclusions.